Materials for design - Lefteri, Chris (Laurence King Publishing, 2013)
Over the last ten years there has been a huge growth in the area of materials for design, but most books on this subject deal with advanced, semi-formed materials (that is, materials sold as sheet, rod, tube, etc.). This book provides much-needed information on the raw materials, and the low-down on how these can be used.